Criminal Liability of Political Parties from the Perspective of Anti-Money Laundering Act (Journal of Indonesian Legal Studies, 2022)
This research addresses the questions on, among other things, criminal liability of political parties from the perspective of the Law on the Prevention and Eradication of Criminal Acts of Money Laundering and the models of criminal liability of political parties with respect to criminal acts of money laundering. The juridical-normative research method used shows that political parties have met the criteria as corporations, being groups of people or assets to which the corporate criminal liability system applies. The fault of a political party in criminal acts of money laundering can be viewed through the actions of its administrators being a systemically integral part of the party as they have been given the roles by the party for the benefit of the party. The first conclusion is that a political party can be held criminally liable for criminal acts of money laundering. Secondly, the models of criminal liability of a political party in criminal acts of money laundering comprise (1) the model of criminal liability under Law No. 8 of 2010 concerning the Prevention and Eradication of Criminal Acts of Money Laundering. (2) Administrative model guided by the principle of systematiche specialiteit and the method of economic analysis of law approach through the Political Party Law. (3) Restorative justice model in the form of dual track system. This model is the alternative companion to the penal justice system, namely the criminal model and administrative model.